2015
DOI: 10.1021/acs.energyfuels.5b00366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Native and Non-Native Resins on Asphaltene Deposition and the Change of Surface Topography at Different Pressures: An Experimental Investigation

Abstract: Asphaltene deposition during oil production and transportation causes extensive damage to reservoirs and wellhead equipment. In this study, the effects of native and non-native resins as well as their mixtures on the asphaltene deposition process are investigated. A novel pressure, volume, and temperature (PVT) visual cell is used to check the effect of resin on asphaltene deposition at different pressures and reservoir temperatures. Two Iranian crude oil samples with different potential of asphaltene depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…As observed by Soorghali et al, the presence of resins changes the way asphaltenes affect the surface, generally leaving the film more homogeneous and less rough. As observed in the characterization, the AP fractions may present a greater amount of coprecipitated resins that are responsible for the variations between the topographies of AH and AP.…”
Section: Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As observed by Soorghali et al, the presence of resins changes the way asphaltenes affect the surface, generally leaving the film more homogeneous and less rough. As observed in the characterization, the AP fractions may present a greater amount of coprecipitated resins that are responsible for the variations between the topographies of AH and AP.…”
Section: Results and Discussionmentioning
confidence: 78%
“…Asphaltenes are formed by aromatic and naphthenic nuclei, aliphatic chains, and heteroatoms, such as oxygen, nitrogen, or sulfur, presenting the highest polarity and molecular weight among petroleum components. Usually asphaltenes are defined as the fraction insoluble in paraffinic hydrocarbons, such as n -heptane, and soluble in aromatics, such as toluene. …”
Section: Introductionmentioning
confidence: 99%
“…Outputs of heavy oil often decreased sharply with the increase of oil viscosity, and stable yields would become hard works when faced with heavy oil with high viscosities. In the last two decades, many studies have been carried on focusing on the structures and compositions of heavy oil 5–12 . It was found that the high content of asphaltenes and resins in heavy oil is the top reason that boosts the growth in viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar context, Labrador et al 22 also conducted studies with toluene−asphaltene solutions of concentrations ranging from 200−10,000 mg/L and reported the thickness of deposited asphaltene films on glass varying in the range of 20−298 nm. In a different study with asphaltene solutions prepared in heptane−toluene mixtures, Soorghali et al 23 reported the roughness of two distinct substrates characterized by AFM to be 168 and 56.6 nm, respectively. The authors stated the difference in roughness as a result of different origins of asphaltene.…”
Section: Introductionmentioning
confidence: 99%
“…The authors stated the difference in roughness as a result of different origins of asphaltene. Both of these individual studies , suggest that asphaltene aging results in a deposition thickness of a few hundred nanometers on glass surfaces, which is also a function of asphaltene concentration.…”
Section: Introductionmentioning
confidence: 99%